2018
DOI: 10.1175/jcli-d-17-0237.1
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Oscillating Southern Hemisphere Westerly Winds: Southern Ocean Coastal and Open-Ocean Polynyas

Abstract: An oscillation in intensity of the Southern Hemisphere westerly winds is a major characteristic of the southern annular mode. Its impact upon the sea ice–ocean interactions in the Weddell and Ross Seas is investigated by a sea ice–ocean general circulation model coupled to an energy balance model for three temporal scales and two amplitudes of intensity. It is found that the oscillating wind forcing over the Southern Ocean plays a significant role both in regulating coastal polynyas along the Antarctic margins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 56 publications
3
13
0
Order By: Relevance
“…We further explore the role of large-scale zonal wind variability by examining its relationship with approximated high-latitude mixed-layer salinity (SALT) anomalies, averaged over the top 100 m of the water column. Our interest in the role of salinity is motivated by observations (Campbell et al 2019) and model simulations (Cheon et al 2014) that demonstrate the triggering of deep convection by high SALT anomalies concurrent with the opposite, positive phase of the SAM (poleward shifted westerlies). First, we find that positive SALT anomalies both within and upstream of the polynya mask region predict polynya heat loss on lag-order time scales of 18-24 months ([SALT, F p ], Fig.…”
Section: A Changes In Atmospheric Surface Propertiesmentioning
confidence: 99%
See 2 more Smart Citations
“…We further explore the role of large-scale zonal wind variability by examining its relationship with approximated high-latitude mixed-layer salinity (SALT) anomalies, averaged over the top 100 m of the water column. Our interest in the role of salinity is motivated by observations (Campbell et al 2019) and model simulations (Cheon et al 2014) that demonstrate the triggering of deep convection by high SALT anomalies concurrent with the opposite, positive phase of the SAM (poleward shifted westerlies). First, we find that positive SALT anomalies both within and upstream of the polynya mask region predict polynya heat loss on lag-order time scales of 18-24 months ([SALT, F p ], Fig.…”
Section: A Changes In Atmospheric Surface Propertiesmentioning
confidence: 99%
“…Reanalysis-based reconstructions of the Weddell polynyas have shown that the tapping of the deep-ocean heat reservoir, combined with intense air-sea interaction over the anomalously ice-free ocean, delivered large quantities of heat to the atmosphere (Moore et al 2002). More recent wintertime observations of smaller polynyas over the Maud Rise seamount during 2016 and 2017 illustrate that these sea ice features can be influenced by high-latitude atmospheric circulation anomalies and strong polar cyclones over the Weddell Sea (Francis et al 2018;Jena et al 2019;Cheon and Gordon 2019;Campbell et al 2019). While both the 1974-76 and 2016-17 events demonstrate connections between deep convection and interannual high-latitude climate variability, observations of open-ocean polynyas in the Southern Hemisphere high latitudes are still sparse.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The adjusted record of changes in the extent of coastal polynyas and sea ice in the Southern Ocean indicate that there is a negative correlation between them.(the sea ice) [23,24]. The open waters of polynyas are also important habitats for birds and marine mammals [8,25,26].Depending on which mechanism forms and maintains polynyas in high latitude oceans, polynyas can be divided into open-ocean and coastal polynyas [1,7,27,28]. The formation of open-ocean polynyas is mainly due to a vertical circulation pattern, known as a "sensible-heat polynya" [1,27,29].…”
mentioning
confidence: 99%
“…Depending on which mechanism forms and maintains polynyas in high latitude oceans, polynyas can be divided into open-ocean and coastal polynyas [1,7,27,28]. The formation of open-ocean polynyas is mainly due to a vertical circulation pattern, known as a "sensible-heat polynya" [1,27,29].…”
mentioning
confidence: 99%